Clinical analysis of 312 patients with stage IB1-IIA2 cervical squamous cell carcinoma and research on the influencing factors of postoperative recurrence - Jia Zeng; Jing Zuo; Ning Li; HongWen Yao; YuanYuan Zhang; YuXi Zhao; TianTian Wang; Lin Xiu; Jian Li; Jing Yu; LeiLei Liang; LingYing Wu (BMC, 2023)
Highlights 1. The relationship between postoperative HPV infection and cervical cancer recurrences was explored for the first time. 2. The genotypes and viral loads of 15 types of HR-HPV were determined. 3. Continuous HR-HPV positivity after surgery and deep 1/3 interstitial infiltration were risk factors for the recurrence of cervical cancer.